Immunologic and structural studies of the lupus/Sjögren's syndrome autoantigen, La/SSB, with a monoclonal antibody. - Harley, J B (1985)
La/SSB is a small nuclear RNA protein against which precipitating autoantibodies are made in many patients with systemic lupus erythematosus or Sjögren's syndrome. The recent purification of La/SSB has made structural and immunologic studies possible. Consequently, a mouse hybridoma antibody (La1) was raised, after immunization and fusion, that reacted with bovine La/SSB. Results of inhibition tests with tissue extracts and fluorescent antinuclear antibody tests demonstrated that La1 reacted with bovine extracts and cells, but not with those from human, mouse, or rabbit sources. La1 reacted in Western blot and in an adapted anti-La/SSB enzyme-linked immunosorbent assay with only the 41-kD bovine La/SSB peptide and not with the smaller 29-kD bovine La/SSB peptide. RNA gels showed that La1 bound the La/SSB particle that contained the predominant La/SSB RNA species near 90 nucleotides as well as the minor RNA species, both of which were bound by the human autoimmune anti-La/SSB serum. A solid-phase assay for human autoimmune anti-La/SSB antibody using La1 was more sensitive for the detection of human anti-La/SSB than was a comparable assay using purified La/SSB, and showed that anti-La/SSB is present in nearly all Ro/SSA precipitin-positive sera. Thus, this study demonstrates that monoclonal antibody can be raised against La/SSB; that the protein moiety of bovine La/SSB differs from human, mouse, and rabbit at an epitope on the 41-kD La/SSB peptide; that the RNA bound to the La1-reactive particle was as heterogeneous as that binding the anti-La/SSB autoimmune serum; and that anti-Ro/SSA and anti-La/SSB are closely associated.